Discovering Mars : a history of observation and exploration of the Red Planet - Sheehan, William, 1954-; Bell, Jim, 1965- (The University of Arizona Press, 2021)
"For millenia humans have considered Mars the most fascinating planet in our solar system. We've watched this Earth-like world first with the naked eye, then using telescopes, and, most recently, through robotic orbiters and landers and rovers on the surface. Historian William Sheehan and astronomer and planetary scientist Jim Bell combine their talents to tell a unique story of what we've learned by studying Mars through evolving technologies. What the eye sees as a mysterious red dot wandering through the sky becomes a blurry mirage of apparent seas, continents, and canals as viewed through Earth-based telescopes. Beginning with the Mariner and Viking missions of the 1960s and 1970s, space-based instruments and monitoring systems have flooded scientists with data on Mars's meteorology and geology, and have even sought evidence of possible existence of life-forms on or beneath the surface. This knowledge has transformed our perception of the Red Planet and has provided clues for better understanding our own blue world."--